The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4269/ajtmh.2011.10-0368
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of Diverse Genotypes of Tahyna Virus in Xinjiang, People's Republic of China

Abstract: Tahyna virus (TAHV) is a member of the California serogroup of the family Bunyaviridae and the genus Orthobunyavirus . Viruses of the genus Orthobunyavirus are arthropod-borne and possess a single-stranded, negative-sense RNA genome of three segments designated small (S), medium (M), and large (L), which encode the nucleocapsid (N), the surface polyprotein, and the polymerase protein, respectively. Tahyna virus was first isolated in Czechoslovakia in 1958 from a pool of Aedes caspius mosquitoes. 1 Since that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…The TAHV IgG titers detected in the current study were over 4-fold higher than those of the other studied orthobunyaviruses in the California serogroup (INKV and CHATV). This is consistent with the view that TAHV is widespread in Europe, 30 Russia, 31 Africa, [32][33][34][35] and Asia (southern Siberia and the Far East, Turkey, Armenia, Azerbaijan, Tadjikistan, Uzbekistan, and China), 30,[36][37][38] whereas INKV and CHATV may be restricted to northern Europe and Asia. 2,30,39 In the endemic region of Europe, approximately 5% of the general population are seropositive for TAHV, 40 and very high frequency (60-80%) of neutralizing antibodies have been reported in elderly persons in the endemic foci.…”
Section: Discussionsupporting
confidence: 76%
“…The TAHV IgG titers detected in the current study were over 4-fold higher than those of the other studied orthobunyaviruses in the California serogroup (INKV and CHATV). This is consistent with the view that TAHV is widespread in Europe, 30 Russia, 31 Africa, [32][33][34][35] and Asia (southern Siberia and the Far East, Turkey, Armenia, Azerbaijan, Tadjikistan, Uzbekistan, and China), 30,[36][37][38] whereas INKV and CHATV may be restricted to northern Europe and Asia. 2,30,39 In the endemic region of Europe, approximately 5% of the general population are seropositive for TAHV, 40 and very high frequency (60-80%) of neutralizing antibodies have been reported in elderly persons in the endemic foci.…”
Section: Discussionsupporting
confidence: 76%
“…in Kashi, Xinjiang, in 2006 (Lu et al 2009 ). Subsequently, TAHV has been isolated from Xinjiang, Qinghai, and Inner Mongolia (Cao YX et al 2011 ; Li W et al 2014 ; Lu et al 2011a ). Phylogenetic analysis generated from N segment and polymerase gene sequences indicated that all TAHV isolates from China group together.…”
Section: Mosquito-borne Viruses Pathogenic To Humans or Animalsmentioning
confidence: 99%
“…Phylogenetic analysis generated from N segment and polymerase gene sequences indicated that all TAHV isolates from China group together. However, the analysis for the M segment showed the isolate XJ0708 aligns independently within the context of a relatively large diversity of isolates from Europe (Lu et al 2011a ).…”
Section: Mosquito-borne Viruses Pathogenic To Humans or Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tahyna virus (TAHV) is a member of the mosquito‐borne virus species, California encephalitis orthobunyavirus ( Peribunyaviridae ), which contains the serologically related California serogroup viruses (e.g., La Crosse virus, Inkoo virus) (Hubálek, ). Two genetic lineages of TAHV are known, one from the European continent (Hubálek, ) and an Asian lineage described from China (Lu et al., ). Genetic variants within the European lineage, which possess biologically different properties, have been identified (Kilian, Růžek, Danielová, Hypša, & Grubhoffer, ; Kilian, Valdes, Lecina‐Casas, Chrudimský, & Růžek, ).…”
Section: Introductionmentioning
confidence: 99%